APA YANG MEMBUAT KARTU KREDIT MENARIK BAGI MILENIAL DAN GEN Z? - Melinda Mokalu; Deske W. Mandagi (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2024)
This research analyzes the factors influencing consumer intentions to use credit cards among Millennial and Gen Z customers. Data was collected through a survey of 200 Millennial and Gen Z credit card users. A self-developed questionnaire consisting of 32 questions was constructed from in-depth interviews with 12 Millennial and Gen Z customers. Data analysis was conducted using exploratory factor analysis (EFA) with varimax rotation and principal component analysis (PCA) to identify the underlying factors shaping consumer intentions. EFA with varimax rotation was chosen to simplify the factor structure, enhancing interpretability by maximizing the variance of squared loadings. PCA was applied as an extraction method to reduce the dataset to its most significant components, offering a clearer understanding of the key dimensions affecting consumer intentions. Findings reveal six important factors, including advertisement effectiveness, customer support, convenience, benefits, brand image, and accessibility, that significantly influence Millennial and Gen Z customers' decisions to use credit cards. These insights provide valuable implications for financial institutions aiming to attract more customers by aligning product offerings and marketing strategies with the expectations and preferences of younger consumers.